The Role of Fishermen’s Joint Business Group (KUB) in Increasing Business Institutional Capacity in Muara Jawa Ilir Village, Muara Jawa District, Kutai Kartanegara Regency. - Muh. Saiful (Multiverse: Open Multidisciplinary Journal, 2022)
The purpose of this study was to measure the role of joint business groups (KUB) in increasing the institutional capacity of fishermen's businesses in Muara Jawa Ilir Village, Muara Jawa District, Kuta Kartanegara Regency. The data collection method in this study is survey research with primary data collection carried out in April 2022 in Muara Jawa Ilir Village, primary data acquisition using a list of questionnaires compiled according to the research objectives. The sample method used is purposive sampling method with data analysis used descriptive quantitative and Liker scale. The results showed that the role of Joint Business Groups (KUB) in increasing the institutional capacity of fishermen's businesses in Muara Jawa ilir Village based on the indicators of the Law of the Republic of Indonesia Number 16 of 2006. The agricultural, fishery and forestry extension system with four indicators of the role of joint business groups as learning media and cooperation vehicles are in the high category while the production unit indicator is in the low category and the business unit indicator is in the medium category overall is in the medium category with an average score of 53.84 in the range of 40.01-56.01.